Rationality and Admiring in Learning from Teacher’s Example: Philosophical and Education Perspective - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2005)
This article deals with a distinction between two teaching methods: rational and irrational. The first one rises from a Socratic dialogue and a questioning tradition and the second one - from the eastern Confucian and Zen tradition, which is more related to teaching from the teacher’s example. The research question is - what is the motivation to follow one’s teacher and his/her examples’! One of the found answers is that the motivation to follow the teacher is inspired by a daemon, which leads to inquiry and searching for the truth. Another one – the admiration of teacher behaviour and mastery, which is very fascinating, but at the same time – irrational. This style is more popular in the Eastern countries. The conclusion about the best features of these methods are the following: the Socratic method should be developed in two directions as critical thinking and as following the teacher’s example, but unfortunately only the teaching of critical thinking is developed at present an eastern method is very useful because of the respect for the teacher, following his examples and at the same time finding one’s way and self-discipline.